2020
DOI: 10.1212/nxi.0000000000000726
|View full text |Cite
|
Sign up to set email alerts
|

Risk of MS relapse after yellow fever vaccination

Abstract: ObjectiveTo determine whether live-attenuated yellow fever vaccine (YFV) was associated with MS relapse, we evaluated the clinical courses of 23 patients in the year before and the year after immunization at the university hospital of Geneva, Switzerland.MethodsThis self-controlled retrospective cohort included adult patients with MS receiving YFV between 2014 and 2018 and defined the year before vaccination, the 3 months thereafter, and the 9 months following as the pre-exposure (PEP), exposure-risk (ERP), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 12 publications
1
26
0
2
Order By: Relevance
“…19 More recently, a small retrospective study reported that yellow fever vaccination was associated with neither an increase in MS relapses nor emergence of brain and/or spinal cord lesions. 20 These contrasting results could relate to differences in the efficacy profile of disease-modifying therapies used soon after yellow fever vaccination and we need further research to establish or exclude any potential causal association. 20…”
Section: Vaccination and Msmentioning
confidence: 99%
See 1 more Smart Citation
“…19 More recently, a small retrospective study reported that yellow fever vaccination was associated with neither an increase in MS relapses nor emergence of brain and/or spinal cord lesions. 20 These contrasting results could relate to differences in the efficacy profile of disease-modifying therapies used soon after yellow fever vaccination and we need further research to establish or exclude any potential causal association. 20…”
Section: Vaccination and Msmentioning
confidence: 99%
“…20 These contrasting results could relate to differences in the efficacy profile of disease-modifying therapies used soon after yellow fever vaccination and we need further research to establish or exclude any potential causal association. 20…”
Section: Vaccination and Msmentioning
confidence: 99%
“…Patients with MS planning travel to yellow fever endemic regions should be encouraged to think carefully about their itinerary. A small study of patients not on highly effective DMTs observed a significant increase in relapse rate following exposure to the yellow fever vaccine, 11 although this was not corroborated in a recent case series 32 . When yellow fever vaccination is essential, DMT cessation with a washout period is required.…”
Section: Individual Vaccinations and Specific Considerationsmentioning
confidence: 98%
“…In comparison, another small study done in 2014–2018 on MS patients in Switzerland showed no association with MS relapses (4 out of 23 patients developed relapses) following YF vaccinations. In addition, as previously discussed, although taking natalizumab and co-administering live-attenuated vaccines is not recommended, none of the patients experienced relapses after YFV or a YFV-related adverse event [ 134 ].…”
Section: Vaccination Overview In the Context Of Multiple Sclerosismentioning
confidence: 99%